Design and Fabrication of Heart Rate and Oxygen Saturation Measurement Device using LED-LED Configuration and to Study Correlation of PPG Signal Amplitude with Breathing Rate (Pakistan Journal of Scientific Research, 2023)
we present an approach for non-invasive signal acquisition in healthcare applications, specifically aiming the measurement of oxygen saturation (SpO2) and heart rate (HR) using photoplethysmography (PPG). Our proposed project emphasis on the design of a circuit that uses light-emitting diodes (LEDs) both as emitters and detectors. Through the use of a Field Programmable Gate Array (FPGA), we are able to effectively control the LEDs. By employing three LEDs, with two serving as emitters and one as a detector, we successfully obtain PPG signal after removing the noise. This work also demonstrates the correlation between PPG signal amplitudes and changes in breathing rate, showing lower amplitudes with decreased oxygen concentration and higher amplitudes with increased breathing rates. This proposed circuit design gives a cost-effective solution with low power consumption, making it highly suitable for practical implementation.
Keywords: Heart rate; light emitting diode; field programmable gate array